The Iran Conundrum: Unraveling India’s Strategic Imperatives in a Shifting Regional Landscape - Narwal, Mohit; Sharma, Rajendra (International Journal of Research in Interdisciplinary Studies, 2025)
The paper explores the complex nature of India's foreign policy involving Iran and the challenges it poses. The paper presents two fundamental ideas—Iran's location as a geopolitical linchpin and India's extended neighborhood—in order to offer a framework for understanding New Delhi's obligations toward Iran in the light of a changing regional and international security environment. The article highlights India's multifaceted considerations in its ties with Iran by discussing five key strategic interests: Engagement with West Asia, Security Dynamics and Stability in the Persian Gulf, Over land access to Central Asia and Russia, Energy Security and Geopolitics of Afghanistan. However, there are a number of complex factors that complicate Indo-Iranian engagement, including Iran's regional activity, the Gulf countries, Israel and the US's reactions to Iranian acts, and the strengthening of strategic ties between China and Iran. As a result, Iran becomes an important strategic puzzle that shapes New Delhi's foreign policy. The present article enhances the sophisticated comprehension of the Iran dilemma and its consequences for India's foreign policy determinations within the Indo-Pacific area.